Measuring the competitiveness of Latvian companies - Arnis Sauka (Baltic Journal of Economics, 2014)
This study makes an empirical contribution by exploring factors that contribute to the competitiveness of Latvian companies. The paper draws on a survey of owner-managers to determine the availability and use of resources and strategies found to be important drivers for firms' competitiveness. Overall, we identify a number of firm-level factors, including involvement in risk-taking behaviour, more extensive use of networking channels, and efficient use of various business strategies as potential sources to increase the competitiveness of Latvian companies. Company owner-managers, however, tend to be more productive in using available human resources, and are satisfied with the availability of physical resources in addition to having a strong export orientation. The study also indicates various shortcomings in the external environment which, as perceived by respondents, are a burden for competitive entrepreneurship activities in the Latvian market. In this light, albeit of an exploratory nature, this study can be used as a source for evidence-based entrepreneurship policies in Latvia and other countries of Central and Eastern Europe.
Keywords: 330; competitiveness; entrepreneurship; Latvia; strategies